Answer:
dy/dx = 18x – 6
Step-by-step explanation:
y = (3x – 1)²
Take derivative using power rule and chain rule:
dy/dx = 2 (3x – 1) × 3
dy/dx = 6 (3x – 1)
dy/dx = 18x – 6
You can check this answer by simplifying y before taking the derivative.
y = 9x² – 6x + 1
dy/dx = 18x – 6
Answer:
F
Step-by-step explanation:
So you would use rise over run so its 4/5 but its negative so you go 4 down and 5 right. So 4 down 5 right is equal to -4/5 which is your slope.
Answer:
48 - 3X
Step-by-step explanation:
( 52+2) - 3x - 6
54 - 3x - 6 So first we deal with the numbers in brackets and that is 52 + 2 giving us 54.
54 - 6 - 3x Then you simplify the expression that is collecting like terms so then we subtract 6 from 54
48 - 3x This is the final expression after simplifying
HOPE THIS HELPED